Ground-penetrating radar and electrical resistivity tomography surveys aimed at the knowledge of the Messapian and Medieval settlement of Ugento (southern Apulia, Italy). Issue 1 (2nd January 2023) - Leucci, Giovanni; De Giorgi, Lara; Ditaranto, Immacolata; Miccoli, Ilaria; Scardozzi, Giuseppe
Abstract : The results of the geophysical surveys carried out in the city of Ugento, specifically in the St. Antonio area and into the Medieval Castle, are presented in this paper. The aim of this study is to integrate the results of Ground-Penetrating Radar and Electrical Resistivity Tomography surveys in order to support archaeological investigations aimed at the elaboration of a detailed archaeological map of the Messapian, Roman and Medieval settlement. Indeed, the obtained data were jointly analysed with archaeological data already known and were georeferenced on the general plans of the site in order to obtain an overall view of the anomalies detected by geophysical instrumentation and related to buried ancient structures. In particular, the geophysical surveys carried out in the St. Antonio area made it possible to reconstruct a stretch of the Messapian city walls and nearby necropolis, while the investigations inside the Castle allowed for the acquisition of very interesting data about previous phases dated to the Middle Ages (and maybe also the Messapian or Roman ages) and about the geo-morphological characteristics of the site.